Clinical Significance of D-dimer and Lipid Profile Alterations in Patients with Heart Disease - Abdulsalam, Rabia Khalid; Shukr, Shahlaa Mahdi; Mahmoud, Huda Mohammed (American Journal of Biology and Natural Sciences, 2025)
D-dimer serves as a biomarker indicating the activation of the coagulation and fibrinolytic systems in reaction to the body’s hypercoagulable condition. This study aimed to evaluate the role of D-dimer in diagnosing patients with dilated cardiomyopathy (DCM) and assessing their risk of developing intracardiac thrombosis, as well as examining its relationship with lipid disorders. DCM patients were compared with a healthy group in terms of D-dimer levels and lipid profiles, which included total cholesterol, triglycerides, low-density lipoprotein (LDL), high-density lipoprotein (HDL), and very-low-density lipoprotein (VLDL). The results showed a significant increase in D-dimer levels in DCM patients compared to the control group, reflecting increased coagulation activity and fibrinolysis, and indicating a higher risk of cardiovascular complications. DCM patients also showed significantly higher levels of total cholesterol, triglycerides, and VLDL, while no significant differences were observed in LDL and HDL levels between the two groups. This suggests that D-dimer may be more closely associated with total cholesterol, triglycerides, and VLDL specifically. These results underscore the importance of D-dimer not only as an indicator of thrombotic activity but also as a factor associated with lipid abnormalities that contribute to the development of cardiovascular disease. Incorporating D-dimer testing into routine cardiac screening may enhance the chances of early detection and support effective therapeutic intervention. To further confirm its diagnostic and prognostic value, the study recommends conducting more comprehensive, multicenter studies with long-term follow-up in patients with heart, liver, and kidney disease.